Impact of national development programs and legislations on the cereal crops seed sector in Iraq - Saloua , ben ammou; Abdulqader, Ammar Mamdooh; Al-Aqidi, Ahmed Muhammad Jassim (Plant Science Today, 2025)
Agriculture is a crucial economic sector in Iraq, benefiting from abundant natural resources, skilled labor and essential infrastructure. These elements have enabled the sector to play a significant role in agricultural development, particularly in the production of strategic crops. Between 2010 and 2020, the Iraqi government implemented various policies and legislation aimed at advancing the seed sector. These efforts focused on supporting and developing seed-producing entities across governmental, mixed and private sectors, positioning them as essential instruments for executing the strategies of the government. Modern agricultural technologies, especially improved seeds, have been vital in boosting productivity and reducing costs. Therefore, the government has prioritized the adoption of advanced technologies within its agricultural policies and programs. These scientific innovations, particularly in seed production, are key to enhancing the cultivation of strategic crops. Improved seeds have thus become a cornerstone of Iraq’s agricultural development, contributing to both increased productivity and sustainable farming practices. This research aims to clarify the role of national development programs and legislation in strengthening the seed sector and increasing the production of strategic crops in Iraq. It reviews the progress in grain crop production between 2006 and 2020 and examines the most significant aspects of government policies, highlighting how legislation and national programs have played a pivotal role in the production of higher-grade seeds and the development of strategic crop cultivation.